Investigating and analyzing the factors and Drivers affecting the convergence and national cohesion (Case study: Baloch people in southeastern country) - abas Jahan Abadian; Yaser kahrazeh; Parviz Reza Mirlotfi (تحقیقات کاربردی علوم جغرافیایی)
Factors and stimuli that influence convergence and divergence play a crucial role in determining the process and quality of national cohesion. These factors and stimuli are not synonymous; rather, they are interconnected and mutually influential variables. Understanding the impact of convergence and national cohesion on overall security is of utmost importance. This study aims to investigate and analyze the factors and stimuli that affect national convergence and cohesion in the southeastern region of the country. Similarly, this article seeks to address the fundamental question of the primary factors and stimuli that influence convergence and cohesion among the Baloch people in the southeast. The research findings indicate that various factors significantly impact the convergence and divergence of the Baloch people in the Sistan and Baluchestan province. These factors can be classified into two categories: internal and external stimuli. The study underscores the significance of factors such as mutual trust, decentralization, concentration of industries and decision-making centers, strengthening ethnic identity in alignment with national identity, the role of historical documents in promoting national cohesion, the cultural center of the Baloch people in southeastern Iran, common social customs, and the positive influence of ethnic and national elites. Additionally, the study recognizes the influence of regional political tensions, historical economic ties with neighboring countries, and the prevalence of border markets with Afghanistan and Pakistan as significant factors that shape convergence, divergence, and national cohesion among the Baloch people in the Sistan and Baluchestan province in the southeast of the country.